Kinerja Pemerintahan Desa Dalam Memberikan Pelayanan Publik Di Desa Serijabo Kecamatan Sungai Pinang Kabupaten Ogan Ilir - Eni Murdiati; Irpinsyah Irpinsyah; Pebri Kurniawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Public service is one of the important aspects in the implementation of village government. However, in practice, there are various problems related to the performance of village government in providing public services. This study aims to identify various factors that influence the performance of village government, as well as supporting factors to improve the quality of public services at the level. The results of the study are expected to provide recommendations to improve the performance of village government in providing better and quality public services for the community. This study will discuss how the Public Service Performance in Serijabo Village, Ogan Ilir Regency. This research approach uses a qualitative approach with a field study research type. Data collection is used by means of observation, interviews and documentation. The object of data collection for this study is in Serijabo Village, Ogan Ilir Regency. The results of this study are that the Serijabo Village Government has carried out its role in administrative services by adopting a bureaucratic structure that is in line with Weber's theory, marked by a clear hierarchy of power and division of labor between the Village Head and other village officials. However, there is still a gap between formal rules and implementation in the field, especially in terms of village apparatus discipline. Factors that influence the performance of Serijabo Village Government in public services consist of three main aspects, namely the quality of human resources, infrastructure, and evaluation and follow-up systems that are not yet optimal.